NATO : from Cold War to Ukraine, a history of the world's most powerful alliance - Rynning, Sten, 1967- 1967- (Yale University Press, 2024)
"For seven decades, NATO's stated aim has been the achievement of world peace—but playing great power politics always involves conflict. Russia's war on Ukraine and on Europe's security order puts the alliance under threat, but also demonstrates why transatlantic cooperation is so necessary. But how did NATO get to where it is today, and what does its future hold? In this incisive new account, Sten Rynning traces the full history of the North Atlantic Treaty Organisation from its origins to the present. Across its seventy-five years, NATO has navigated the twists and turns of Cold War diplomacy and nuclear deterrence, and has grown its membership. The alliance has become a guarantor of peace, but Rynning explores how its complex inner workings alongside Russian and Chinese opposition are now shaping its direction. At a time of strategic competition and geopolitical upheaval, Rynning offers us a clear-sighted account of the alliance's intriguing history—and asks what its ambitions might be for the future." -- Verlagswebsite